STRATEGI BERTAHAN HIDUP BURUH HARIAN LEPAS DALAM MEMENUHI KEBUTUHAN POKOK KELUARGA DI KELURAHAN TANJUNGBATU BARAT KECAMATAN KUNDUR KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Kurnia Wati; Deded Chandra (JURNAL BUANA, 2022)
The aim of this research is to determine the survival strategy of casual daily workers in meeting the basic needs of families in Tanjungbatu Barat Village, Kundur District, Karimun Regency, Riau Archipelago Province. The type of research used in this research is descriptive type with a qualitative approach. The data collection technique in this research is by using interview observation and documentation. The informants involved in this study were 22 informants who worked as casual daily laborers. Data analysis used is data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that there are three strategies used by casual daily workers to survive, namely: active strategy, passive strategy and network strategy. The active strategy carried out by casual daily workers is to look for side jobs in order to get additional income in order to meet the needs of the family starting from working as a construction worker, motorcycle taxi driver, raising chickens, cattle labor and odd jobs . The passive strategy carried out by casual daily workers is to apply a frugal lifestyle. The network strategy used by casual daily workers is to ask for help from the social networks they have, both formal and informal networks.